Evaluation Degradation of Bioactive Compounds of Fruit Physalis (P. peruviana) During the Drying Process (Research, Society and Development, 2020)
The objective of this study was to perform the drying kinetics of fruit physalis, verifying the fit of the empirical mathematical models to the experimental data obtained and to evaluate the influence of the different temperatures used in the process in relation to its centesimal composition and bioactive compounds. Drying kinetics were performed using a fixed air velocity convective dryer (1.5 m.s-1) and temperature ranging from 40 to 70 °C. In fresh and dehydrated fruits, moisture content, ash, lipids, protein, total carbohydrates, anthocyanins, flavonoids, total carotenoids, total phenolic compounds and antioxidant activity (ABTS+ and DPPH) were determined. Among the studied mathematical models, the Silva et ali. model presented the best fit to the experimental data, with coefficient of determination (R2> 0.99) and chi-square values (